Political discourse of excess in times of crisis: populist vocabulary of presidential candidates in Chile and Colombia (2021-2022) - Santamaría-Velasco, Freddy; Restrepo-Echavarría, Néstor Julián; Ramírez-Vallejo, Dora A. (Infonomy, 2025)
On December 19, 2021, Chileans elected Gabriel Boric as their country's first president. Six months later, on June 19, 2022 in the Colombian presidential elections, the winner was Gustavo Petro. Although they are different countries in Latin America, both had similar electoral contexts caused by the socioeconomic crisis left by the Covid-19 pandemic, the social mobilizations and protests of different sectors of society, the rejection of traditional politics and institutions, and an electoral contest with different characters; among which, some promised to solve this increasingly growing dissatisfaction among citizens. This article analyzes the electoral speech of Gabriel Boric and José Antonio Kast in Chile and Gustavo Petro and Rodolfo Hernández in Colombia, in order to identify the discursive excesses that these political leaders used to take advantage of the context of crisis and exalt their political figure to obtain electoral victory. A political discourse analysis methodology was used with codes and categories that configure a populist vocabulary, and then the sample was reviewed using Python natural language processing.
Keywords: Latin American crisis; Latin America; Analysis of political discourse; Populism; Presidential elections; Electoral contests; Populist vocabulary; Chile; Colombia